Effect of Six Lactic Acid Bacteria Strains on Physicochemical Characteristics, Antioxidant Activities and Sensory Properties of Fermented Orange Juices - Quan, Qi; Liu, Wei; Guo, Jiajing; Ye, Meiling; Zhang, Juhua (Foods, 2022)
Six lactic acid bacteria strains were used to study the effects on physicochemical characteristics, antioxidant activities and sensory properties of fermented orange juices. All strains exhibited good growth in orange juice. Of these fermentations, some bioactive compositions (e.g., vitamin C, shikimic acid) and aroma-active compounds (e.g., linalool, 3-carene, ethyl 3-hydroxyhexanoate, etc.) significantly increased in Lactiplantibacillus plantarum and Lactobacillus acidophilus samples. DPPH free radical scavenging rates in L. plantarum and Lacticaseibacillus paracasei samples increased to 80.25% and 77.83%, respectively. Forty-three volatile profiles were identified, including 28 aroma-active compounds. 7 key factors significantly influencing sensory flavors of the juices were revealed, including D-limonene, linalool, ethyl butyrate, ethanol, β-caryophyllene, organic acids and SSC/TA ratio. The orange juice fermented by L. paracasei, with more optimization aroma-active compounds such as D-limonene, β-caryophyllene, terpinolene and β-myrcene, exhibited more desirable aroma flavors such as orange-like, green, woody and lilac incense, and gained the highest sensory score. Generally, L. paracasei fermentation presented better aroma flavors and overall acceptability, meanwhile enhancing antioxidant activities.